Model Pembelajaran Quantum Teaching Untuk Meningkatkan Hasil Belajar Matematika Siswa Sekolah Dasar - Yunita Wildaniati (Jurnal Dewantara, 2017)
This research is done giving effort to improve student learning achievement by using Quantum Teaching learning model in Classroom Action Research. From the results of the analysis can be concluded that the learning model of quantum teaching can improve the completeness of mathematics learning outcomes of elementary school students. From the result of research, the result of learning result in cycle I is pretest 54,16% and posstest 66,67% while in cycle II the result of pretest learning is 45,83% and posttest 83,33% with medium criterion . So the level of completeness of student learning outcomes from cycle I and cycle II increased 16, 66%, then the desired target has been achieved for student learning completeness at the end of the cycle has exceeded the specified target of 70%. This can be seen from the percentage of students who complete learning in cycle I of 66.67% and cycle II of 83.33%.